What influences healthcare professionals' treatment preferences for older women with operable breast cancer?: an application of the discrete choice experiment - Morgan, J.L.; Walters, S.J.; Collins, K.; Robinson, T.G.; Cheung, Kwok-Leung; Audisio, R.; Reed, M.W.; Wyld, L. (Elsevier, 2017)
Introduction